MODELING HOCN-HNCO ISOMERIZATION THROUGH COMPUTATIONAL STUDIES - Hasby
The HOCN-HNCO isomerization is a simple reaction, but it has two reaction pathway, both of them are 1,3-H shift and it has more complex migration atom processes. The process contains a lot of information on the fundamental aspects of the structure and electronic properties, thermodynamics, and kinetics. The purpose of this research is to study the HOCN-HNCO isomerization seen from the aspect of the structure and electronic properties, thermodynamics and kinetics through computational studies. The results of modeling reaction through computational studies have also been applied in the form of lab module. The lab module is expected to help the students know the phenomena in chemical reactions, which cannot be seen directly from the experiments. All levels of calculations performed by computational methods approach DFT, B3LYP functional, and used different of basis sets, both 6-311G(d) and cc-PVTZ are as a comparison. The obtained calculation result is then processed and validated by comparing it to experimental data and previous studies. The results of computational calculations show that the structure of HNCO (product) is more stable than the reactants. This is in accordance with the value of Gibbs free energy of the reactants and products are - 168.660 hartree and -168.709 hartree for the basis sets B3LYP/6-311G(d), - 168.686 hartree and -168.732 hartree for the basis sets B3LYP/cc-PVTZ, respectively. This is also supported by the value of the HOMO and LUMO energy difference of reactant and product are 7.9768 eV and 8.5423 eV for the basis set B3LYP/6-311G(d), 8.0124 eV and 8.5613 eV for the basis sets BLYP/cc-PVTZ, respectively. Value of ?Horeaction is -128.469 kJ/mol for the basis sets B3LYP/6- 311G(d) and -120.358 kJ/mol for the basis sets B3LYP/cc-PVTZ. These results indicate that the reaction is exothermic and enthalpy of the products is lower than the enthalpy of the reactants, then during the reaction is accompanied by releasing heat process. Results obtained for the ?Goreaction is also negative (-) in both of calculation basis set used. Based on the resulting data, the HOCN-HNCO isomerization can take place spontaneously. In thermodynamics and kinetics reaction, pathway through TS1 is more preferable than the reaction pathway through TS2. Activation energy (Ea) for TS1 and TS2 are 250.077 kJ/ mol and 578.381 kJ/mol for the basis sets B3LYP/6-311G(d) and 253.363 kJ/mol and 463.498 kJ/mol for the basis sets B3LYP/cc-PVTZ, respectively. Lab module “Isomerization of simple molecules and visualization”, the output of the results of